Prevalence of smoking (cigarette and waterpipe) and its association with obesity/overweight in UAE and Palestine - Al Sabbah, Haleama; Assaf, Enas A.; Dabeet, Elias (Frontiers in Public Health, 2022)
Aim: This study aimed to assess the prevalence rate of smoking behavior (cigarette and water-pipe) and its association with obesity/ overweight among university students in the United Arab Emirates (UAE) and Palestine. Methods: A cross-sectional study was conducted at 5 universities in the West Bank- Palestine and 5 universities in Dubai- UAE. In total, 3800 students were randomly selected from the universities, with an 87.6% response rate. A self-administered questionnaire was used to collect the data. The key measures were: water pipe smoking, weight, height, cigarette smoking, dieting to reduce weight, and perception and knowledge related to tobacco water pipe smoking (TWP). Body Mass Index (BMI) was calculated using the WHO cutoffs. Results: The analysis included 3327 students (54% from the West Bank and 46% from Dubai). 16% of students in Dubai and 18% of students in West Bank smoke cigarettes. About quarter (26%) of the students in Dubai and 32% of the students in West Bank smoke water pipes. 17% of students in Dubai and 18% of students in West Bank reported that they smoke water-pipes to reduce their weight. Water pipe smoking was found to have a significant positive association with obesity/overweight (p< 0.001). Conclusions: Smoking is very common among university students. Water pipe smoking was associated with obesity. More research is still needed in this field to better understand the relationship between cigarette smoking and obesity.